Management of extensive surgical wounds of the extremity after tumour resections using two simultaneous composite flaps: two case reports - Faizal A; Ahmad SH; Zulmi W (Department of Surgery, UKM Medical Centre, 2011)
Tumour surgery for locally extensive malignant neoplasms of the extremity will sometimes result in extensive composite soft tissue defect. Local flaps are usually inadequate to cover these large defects. More than one tissue flap might be required to cover any exposed neurovascular structures, bone or prosthesis. We present two cases where two composite flaps were simultaneously used to cover extensive surgical defects after ablative tumour resections in the extremity. These resulted in uncomplicated wound healing and limb salvage.